Effect of Liquidity, Profitability, and Solvency on Stock Returns of Non-Cyclical Consumer Manufacturing Firms on IDX 2021–2023 - Widianto, Afin; Bagana, Batara Daniel (Golden Ratio of Finance Management, 2025)
This study aims to examine and investigate the factors that influence stock returns. The variables analyzed in this study include liquidity, profitability, and solvency. The study population consists of manufacturing companies in the Consumer Non-Cyclical sector listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. This study employs a quantitative approach, utilizing secondary data analysis. Sampling was conducted using a purposive sampling method, resulting in an initial sample of 127 companies with a total of 270 observations. During the data processing process, several outliers were identified, so they were removed, resulting in 123 valid observations. The analytical approach employed was quantitative, used to examine the relationship between variables. The results show that liquidity and solvency have a significant positive effect on stock returns.